Living with the Past in the Present – Korean Furniture and Home Décor Design at the Milan Design Week - Rossi, Jessica (ITB Journal Publisher, DRPM ITB, 2025)
This article traces the historical outline of the development of design in South Korea. Foreign policies promoting Korean design will be discussed as evidence of the importance of K-design exports and to introduce the collaboration between Italian and Korean designers at Salone del Mobile. In 2023, the Korean government’s direct participation in Milan Design Week marked the 11th year of the Korea Craft and Design Foundation’s (KCDF) participation in the Italian international fair. Each year, the foundation curates an exhibition showcasing Korean furniture and home décor which exemplify the fusion of traditional Korean craftsmanship and contemporary design sensibilities. Notably, for the 60th anniversary of the Salone del Mobile in 2022, KCDF planned a special exhibition bridging Italian and Korean design cultures. This initiative facilitated a direct collaboration between Italian designer Francesco Faccin and Korean artisan Hur Sung-Ja, resulting in the realization of three projects. These projects serve as a benchmark for the reimagining and internationalization of traditional Korean crafts, epitomizing the concept idea of K-crafts. This article innovatively investigates the topic of Korean traditional crafts, highlighting the Korean government’s domestic policies aimed at promoting internationalization. Such policies seek to enhance Korean influence globally and strategically shape the future of K-Crafts.